Characterization of mitochondrial mRNAs in codfish reveals unique features compared to mammals - Coucheron, Dag-Hugo; Nymark, Marianne; Breines, Ragna; Karlsen, Bård Ove; Andreassen, morten; Jørgensen, Tor Erik; Moum, Truls; Johansen, Steinar Daae (Current Genetics, 2011)
Expression and processing of mitochondrial gene transcripts are fundamental to mitochondrial function, but information from early vertebrates like teleost fishes is essentially lacking. We have analyzed mitogenome sequences of ten codfishes (family Gadidae), and provide complete sequences from three new species (Saithe, Pollack and Blue whiting). Characterization of the mitochondrial mRNAs in Saithe and Atlantic cod identified a set of ten poly(A) transcripts, and six UAA stop codons are generated by posttranscriptional polyadenylation. Structural assessment of poly(A) sites is consistent with an RNaseP cleavage activity 5′ of tRNA acceptor-like stems. COI, ND5 and ND6 mRNAs were found to harbor 3′ UTRs with antisense potential extending into neighboring gene regions. While the 3′ UTR of COI mRNA is complementary to the tRNASer (UCN) and highly similar to that detected in human mitochondria, the ND5 and ND6 3′ UTRs appear more heterogenic. Deep sequencing confirms expression of all mitochondrial mRNAs and rRNAs, and provides information about the precise 5′ ends in mature transcripts. Our study supports an overall evolutionary conservation in mitochondrial RNA processing events among vertebrates, but reveals some unique 5′ and 3′ end characteristics in codfish mRNAs with implications to antisense regulation of gene expression.